Thorium and Total REE Correlation in Stream Sediment Samples from Lingga Regency - Irzon, Ronaldo (BRIN Publishing, 2018)
Rare Earth Elements (REE) are found in variety of minerals, which are mobilized by weathering from adjacent watersheds into streambeds and affect the chemical content. A study of stream sediments is useful to trace the source of metals, as they are representative of the composition of the drainage basin. This study describes trace and rare earth elements geochemistry composition of selected nine stream sediment samples from two major Islands in Lingga Regency, namely Singkep and Lingga. Moreover, the associations of rare earth elements abundance to other elements in selected samples are used on tracing the most possible mineral as REE source. Nine selected stream sediments were identified megascopically and measured for the trace and rare earth elements composition by inductively coupled plasma – mass spectrometry (ICP-MS). The selected samples from Lingga yielded very strong average Zr, Mn, Ba, and Rb compositions of 246 ppm, 172 ppm, 126 ppm, and 84 ppm, respectively. On the other hand, Zr, Mn, Cr, and Rb are the top four abundant trace elements from Singkep with consecutive median value of 486 ppm, 305 ppm, 145 ppm, and 85 ppm. Feltilizer for agricultural area at Lingga most posibly contain As and Rb upon these elements abundances and association. Tin mine activity was found to influence the streambeds composition with low Rb-Cs composition but high Zr-REE abundance. Very strong Th to ∑REE association suggests that thorium-bearing mineral, especially monazite-La, is the main REE source of the selected samples. All of the studied samples exhibit Eu negative anomaly to imply the absence of either detrital apatite or chemical weathering of apatite. Moreover, REE of Lingga stream sediments is averagely more fractionated than Singkep.